Brentuximab vedotin use in pediatric anaplastic large cell lymphoma - Agrusa, Jennifer E.; Egress, Emily R.; Lowe, Eric J. (Frontiers in Immunology, 2023)
Anaplastic large cell lymphoma (ALCL) is the most common type of mature T-cell non-Hodgkin lymphoma in children/adolescents. ALCL is characterized by expression of CD30 in the neoplastic lymphoid cells with frequent expression of anaplastic lymphoma kinase (ALK), especially within the pediatric population. Despite multiple efforts to optimize the use of conventional chemotherapy, outcomes in children, adolescents, and adults with ALCL remain suboptimal. Thus, there is a need to improve survival for those with high-risk disease and decrease therapy exposures and toxicities for those with low-risk disease. Targeted therapies, such as the anti-CD30 antibody-drug conjugate, brentuximab vedotin, are new important therapeutic options. Phase I and II studies in adults with relapsed/refractory CD30+ lymphomas, including ALCL, demonstrated the safety and efficacy of brentuximab vedotin, leading to FDA approval for relapsed/refractory ALCL in adults and successful incorporation into frontline therapies. Clinical trials in the pediatric population demonstrated similar results in those with relapsed/refractory ALCL. Incorporation of brentuximab vedotin into upfront therapy for children and adolescents with ALCL showed that this novel combination therapy has clinical advantages in comparison to conventional agents alone. Brentuximab vedotin is well-tolerated in both the pediatric and adult populations, even when used in combination with conventional agents. Brentuximab vedotin is an ideal agent to treat ALCL with excellent targeted activity and limited toxicity. Future studies are needed to identify how brentuximab vedotin should be utilized when combined with immunotherapy or other targeted agents (e.g., ALK inhibitors) in both the upfront and relapsed/refractory setting.